2017
DOI: 10.19044/esj.2017.v13n31p438
|View full text |Cite
|
Sign up to set email alerts
|

Role of Dynamic Capabilities in the Performance of Manufacturing Firms in Nairobi County, Kenya

Abstract: The advent of globalization has brought with it drastic changes to the operating landscape for firms in the manufacturing sector. The need for transformational changes so as sustain competitive advantage has been on the rise. Firms are expected to continuously re-engineer their business models and operations to catch up with the turbulent environment. Previous studies have investigated the contribution of manufacturing firms in economic growth. Some have concentrated on the preferred approaches that countries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 57 publications
3
13
2
Order By: Relevance
“…Thus these results are supported by a significance value for the dynamic capability dimension sensing (DCS) variable of 0.019 <0.05, this indicates that there is an effect of dynamic capability sensing dimension (DCS) with sustainable tourism performance (SP). The results of this study support previous studies that have been conducted which provide the same research results as research by [16], [17], [25] who say that the dynamic capability of the sensing dimension has an influence on tourism performance. Sustainable (SP)  The dynamic capability dimension seizing (DCSZ) variable has an effect on sustainable tourism performance (SP), the test results show that the coefficient of direct influence of dynamic capability dimension seizing (DCSZ) on sustainable tourism performance (SP) is 0.416, meaning the dynamic capability variable The seizing dimension (DCSZ) has a positive relationship with the variable on sustainable tourism performance (SP), this result provides information that the better the dynamic capability of the seizing dimension (DCSZ), as it can quickly relate to new knowledge from outside, new information can be used for management.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus these results are supported by a significance value for the dynamic capability dimension sensing (DCS) variable of 0.019 <0.05, this indicates that there is an effect of dynamic capability sensing dimension (DCS) with sustainable tourism performance (SP). The results of this study support previous studies that have been conducted which provide the same research results as research by [16], [17], [25] who say that the dynamic capability of the sensing dimension has an influence on tourism performance. Sustainable (SP)  The dynamic capability dimension seizing (DCSZ) variable has an effect on sustainable tourism performance (SP), the test results show that the coefficient of direct influence of dynamic capability dimension seizing (DCSZ) on sustainable tourism performance (SP) is 0.416, meaning the dynamic capability variable The seizing dimension (DCSZ) has a positive relationship with the variable on sustainable tourism performance (SP), this result provides information that the better the dynamic capability of the seizing dimension (DCSZ), as it can quickly relate to new knowledge from outside, new information can be used for management.…”
Section: Discussionsupporting
confidence: 89%
“…Research by [17] shows that sensing capabilities, seizing capabilities, and reconfiguration capabilities affect the performance of manufacturing companies in Kenya. However, other studies show different results such as research by [18] dynamic integration capability has no effect on performance, dynamic learning capability has no effect on performance and dynamic reconfiguration capability has no effect on performance.…”
Section: Sustainable Business Performance Businessmentioning
confidence: 99%
“…Similarly, Engelen et al (2015) (Mansouri, 2016). Similar findings have also been reported in a study conducted by Nyachanchu et al (2017), when they conducted a study on 271 manufacturing facilities.…”
Section: Background and Hypotheses Developmentsupporting
confidence: 85%
“…Key respondents used in the study were chief executive officers (CEOs). Regression analysis conducted by Nyachanchu et al (2017) revealed, collectively, dynamic capabilities account for about 25.9% of variation in the performance of manufacturing companies in Kenya. However, each of the three dimensions (reconfiguration: B=0.182, p<0.001; sensing: B=0.215, p<0.01; and seizing: B=0.194, p<0.01) showed significant relationship with the performance of manufacturing firms.…”
Section: Factors Affecting Manufacturing Sub-sector's Performance and Growthmentioning
confidence: 99%